2022
DOI: 10.48550/arxiv.2207.12996
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Role of the edges in a quasicrystalline Haldane model

Abstract: We study the role of the edges in determining the features of the topological phase in a quasicrystalline higher order topological insulator. We consider a specific model consisting of two stacked Haldane models with opposite Chern number and a 30 • twist, whose structure is cristallographically equivalent to that of the graphene quasicrystal. We find that the gap-opening in the low energy spectrum of the higher order topological insulator occurs at different energies when different kinds of edges are consider… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…We then crop our lattice with a square shape centered in the rotation center, and oriented in such a way that the edges are not jagged. As already noted in [72], the edges of the resulting system-which possesses C 4 global rotational symmetry -can only be given by two possible pairs of the upper and lower layer edges: bearded-armchair or zigzagarmchair. However, even once the combination of the edges has been chosen, there are still two families of square lattices that can be obtained: these differ with each other for the disposition of the lattice sites around the vertices 1 .…”
Section: Latticementioning
confidence: 88%
See 3 more Smart Citations
“…We then crop our lattice with a square shape centered in the rotation center, and oriented in such a way that the edges are not jagged. As already noted in [72], the edges of the resulting system-which possesses C 4 global rotational symmetry -can only be given by two possible pairs of the upper and lower layer edges: bearded-armchair or zigzagarmchair. However, even once the combination of the edges has been chosen, there are still two families of square lattices that can be obtained: these differ with each other for the disposition of the lattice sites around the vertices 1 .…”
Section: Latticementioning
confidence: 88%
“…The result is that the system, thanks to the presence of the rotational symmetry, hosts topological bound states, which are degenerate, isolated in energy from the others, and localized at the vertices of the structure. A subsequent work [72] showed that these properties also characterize samples with armchair-zigzag edges. However, in this case, the energy at which the gap opens drastically changes.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…The system is hence a higher order topological insulator with d = 2 and n = 2. A subsequent work [72] showed that these properties also characterize samples with armchairzigzag edges. However, in this case, the energy at which the gap opens drastically changes.…”
Section: Introductionmentioning
confidence: 92%